Regulatory mechanisms of intestinal iron absorption: Iron-deficient mucosal cells respond immediately to dietary iron concentration - Shoko Shinoda; Anna Arita (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Iron is a nutrient and its deficiency is the most frequent nutritional disorder worldwide, occurring in 4 to 5 billion people corresponding to about 70-80% of the world's population as estimated by the World Health Organization. However, an excess of iron increases oxidative stress and increases the risk of death and cancer; thus blood transfusion and supplementation should be used with caution. As there is no mechanism for deliberate iron excretion, the regulation of iron absorption in the small intestine is required to maintain total body iron balance and prevent excessive or deficient iron levels. Proteins involved in intestinal iron absorption were first identified in 1997. Molecular mechanisms of iron transport from the lumen of the small intestine to the portal blood through epithelial cells have been elucidated. In addition to long responses to iron deficiency in vivo, a short response exists for iron concentrations in the small intestine. This review describes regulatory mechanisms at the forefront of iron absorption, focusing on short acting mucosal block.